ANALISIS VISUAL PERFORMA PENILAIAN MASSAL DALAM MENENTUKAN NILAI JUAL OBJEK PAJAK (NJOP) PROPERTI PERUMAHAN DAN PROPERTI KOMERSIAL (STUDI KASUS : KECAMATAN BOJONGLOA KALER DAN BABAKAN CIPARAY, KOTA BANDUNG) - Ikhsan
The one of another real property tax characteristics is favorable treatment residential property over business property (Slack:2001). Many rules of Indonesian property tax (PBB), hasn't yet facility for that. That why, the most possibility, a positive tax treatment of residential property has often been achieved through disproportional valuation in assessment practices (Youngman, 1999). The capital or "sales" value of the tax object (NJOP- Nilai Jual Objek Pajak) obviously just as a basic collection of property tax that used in many needs. That why, if distinction in assessment level between property type occurred, it will cause economic inefficiency dan contradictory in fairness dan equity in property tax system. To prove the distinction assessment level and the same time improve valuation system, so will be needed to make mass appraisal performance analysis. The result from 86 samples examination (54 housing, 32 commercial), in Kecamatan Bojongloa Kaler and Babakan Ciparay, obtained assessment ratio (AR) housing property in average is 63,3% dan commercial property 56,2%. In variability calculation (individual uniformity in property group) obtained coefficient of dispersion (COD) housing 27,3% and 18,5% COD commercial property. The value of COD housing property is higher than maximal standar (15%), so it must be revaluation. The result of difference two sample mean test (t test) obtained, there is no significant distinction assessment level between housing and commercial properti. In the result of level assessment test (one sample test) in Ho hypothesis 63,9% commercial property is in under hypothesis level. From the overlay analysis between land value map dan property classification map, provide evidence in land valuation (delimiting land value zone (Zona Nilai Tanah-ZNT)) less considering land use factor. That why, it makes average AR of commercial property lower than the others.